Sliding Mode Controller-based Load Frequency Regulation for a Two-area Interrelated Power System - K. Durga Syam Prasad; K. Sravanthi (International Journal of Advanced Control and System Engineering, 2024)
This study presents the use of the sliding mode control approach for power systems load frequency regulation. A sliding mode load frequency controller is part of a two-area power system. Both reheat and non-reheat. These two regions each have a distribution of thermal turbines. Nonlinearities such as governor dead region and production rate limitations are included in the block diagram of a power plant model. Our control objective is to manage the power system's load frequency inaccuracy when various load variations and parameter variations occur. The sliding mode controller (SMC) is modelled using a two-area integrated power system with nonlinearities. The sliding mode controller's robustness is demonstrated by these simulation findings. Furthermore, it demonstrates how tie line power errors and frequency mistakes converge to zero. Sliding mode controller performance is contrasted with fuzzy, PID, and traditional PI controllers. These comparisons demonstrate that SMC outperforms the other controllers in terms of effectiveness and insensitivity to parameter changes.
Keywords: Governor dead band; Load frequency control; generation rate constant; sliding mode controller